Evidence for a Mixed Timing and Counting Strategy in Mice Performing a Mechner Counting Task - Light, Kenneth R.; Cotten, Brian; Malekan, Talia; Dewil, Sophie; Bailey, Matthew R.; Gallistel, Charles R.; Balsam, Peter D. (Frontiers in Behavioral Neuroscience, 2019)
Numerosity, or the ability to understand and distinguish between discrete quantities, was first formalized for study in animals by Mechner in 1958. Rats had to press one lever (the counting lever) n times to arm food release from pressing a second lever (the reward lever). The only cue that n presses had been made to the counting lever was the animal’s representation of how many times it had pressed it. In the years that have passed since, many researchers have modified the task in meaningful ways to attempt to tease apart timing-based and count-based strategies. Strong evidence has amassed that the two are fundamentally different and separable skills but, to date, no study has effectively examined the differential contributions of the two strategies in Mechner’s original task. By examining performance mid-trial and correlating it with whole-trial performance, we were able to identify patterns of correlation consistent with counting and timing strategies. Due to the independent nature of these correlation patterns, this technique was uniquely able to provide evidence for strategies that combined both timing and counting components. The results show that most mice demonstrated this combined strategy. This provides direct evidence that mice can and do use numerosity to complete Mechner’s original task. A rational agent with fallible estimates of both counts made and time elapsed in making them should use both estimates when deciding when to switch to the second lever.